KEPUTUSAN PEMBELIAN BERBASIS MARKETING MIX DI MODERASI SERTIFIKASI HALAL - Muhammad Arif; Irwan Syari Tanjung; Nafisah Azzharoh Nasution (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine and analyze the Marketing Mix-Based Purchase Decision in Moderation of Halal Certification. This study uses Marketing Management theory related to Product, Price, Place, Promotion, Purchase Decision and Halal Certification. The approach used in this study is to use an associative approach and the type of data used is quantitative. The population in this study are consumers / visitors to the Marelan Culinary Barn whose number is unknown. The number of samples as many as 60 visitors using simple random sampling technique. The data analysis technique used in this research is Partial Least Square (PLS). The results showed that the product did not have a positive and insignificant effect on purchasing decisions, price had no positive and insignificant effect on purchasing decisions, place had no positive and insignificant effect on decisions, promotions had a positive and significant effect on purchasing decisions, and halal certification had no positive effect. and not significant to Purchase Decision, Halal Certification does not moderate the Product variable to Purchase Decision, Halal Certification does not moderate the Price variable to Purchase Decision, Halal Certification does not moderate the Place variable to Purchase Decision and Halal Certification does not moderate the Promotion variable to Purchase Decision.